Stimulus Minat Belajar Matematika Menggunakan Media Pembelajaran Audio Visual di Tingkat Sekolah Dasar - Rahayu, Nina; Fahmi, Khairul; Alparisi Efendi, Salman; Wulandari, Febriyantika (Mulya Literasi Publishing, 2024)
This article describes the skills of students in learning mathematics by using media and audio in madrasah/primary schools in Ibtidaiyah. This study aims to determine the use of these communication tools on students' interest in learning mathematics. This research is qualitative research using the SLR (Systematic Literature Review) method. Data sources are 10 journal articles indexed by Google Scholar. Data analysis was carried out with the stages of data collection, data reduction, verification, and conclusion drawing. This research was conducted in elementary schools to see the use of audio and digital media in learning mathematics. The results of this study show that audio and video media can increase students' interest in learning mathematics. Students learn math through these two methods compared to traditional teaching methods. The use of audio and digital media can increase students' participation in the learning process. In addition, students can better understand difficult and complex mathematical concepts because of the access provided by both media. The results provide important implications for curriculum development at the Primary level and recommend the inclusion of audio and digital media in mathematics education. This research makes an important contribution to improving the quality of mathematics teaching and students' interest in the course. This research is also expected to provide a reference for developing new interactive teaching methods at the elementary school level.